'If I donate my organs it's a gift, if you take them it's theft': a qualitative study of planned donor decisions under opt-out legislation - Jordan Miller; Sinéad Currie; Ronan E. O'Carroll (BMC, 2019)
Abstract Background There is a worldwide shortage of donor organs for transplantation. To overcome this, several countries have introduced an opt-out donor consent system. This system, soon planned for Scotland and England means individuals are automatically deemed to consent for organ donation unless they register an opt-out decision. This study was designed to explore the reasons underpinning donor choices for people who plan to actively opt-in to the register, take no action and be on the register via deemed consent, opt-out, and those who are unsure of their decision. Methods This study reports the analysis of free-text responses obtained from a large survey of intentions towards opt-out legislation in Scotland, England and Northern Ireland (n = 1202). Of the n = 1202 participants who completed the questionnaire, n = 923 provided a free text response explaining their views. Thematic analysis was used to explore the reasons why participants plan to: opt-in (n = 646), follow deemed consent (n = 205), opt-out (n = 32) and those who were not sure (n = 40). Results A key theme for people planning to opt-in is that it ensures one's donor choice is explicitly clear and unequivocal. Some regarded deemed consent as unclear and open to ambiguity, thus actively opting-in was viewed as a way of protecting against family uncertainty and interference. For the deemed consent group, a key theme is that it represents a simple effortless choice. This is important from both a pragmatic time-saving point of view and because it protects ambivalent participants from making a challenging emotive choice about organ donation. Key themes for those planning to opt-out relate to fears around medical mistrust and bodily integrity. Notably, both participants who plan to opt-out and opt-in perceived presumed consent as "authoritarian" and a method of increasing Government control of organs. In response, registering an active decision protected their freedom of choice. Conclusions The findings highlight the importance of registering deliberate active consent for people who choose opt-in, due to concerns over possible family refusal under deemed consent. These findings could inform the development of communication campaigns that encourage family communication before the implementation of opt-out legislation.